1986
DOI: 10.1148/radiology.161.1.3763873
|View full text |Cite
|
Sign up to set email alerts
|

Gaucher disease: assessment with MR imaging.

Abstract: The skeletal system, spleen, and liver of five patients with proved Gaucher disease were studied with magnetic resonance (MR) imaging. Homogeneous, low intensity signals resulting from relaxation times different than normal (longer T1 and shorter T2 values) were found in the marrow of long bones, vertebrae, and hips in all patients. In three patients, normal signals were noted in the patella, epiphysis of the knee, and capital femoral epiphysis. In two patients with acute bone pain in the tibial region, a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
2

Year Published

1991
1991
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 0 publications
2
22
2
Order By: Relevance
“…The epiphysis, however, was involved in six of the 16 patients in group B and seven of the nine patients in group C. In general, our findings correspond with those of Lanir et al [15] and Rosenthal et al [16], who reported that the epiphyses were generally spared unless the involvement of bone was extensive.…”
Section: (Arrows)supporting
confidence: 91%
See 3 more Smart Citations
“…The epiphysis, however, was involved in six of the 16 patients in group B and seven of the nine patients in group C. In general, our findings correspond with those of Lanir et al [15] and Rosenthal et al [16], who reported that the epiphyses were generally spared unless the involvement of bone was extensive.…”
Section: (Arrows)supporting
confidence: 91%
“…Some patients may have a diffuse infiltration and others may have a patchy infiltration, with islands of preserved fatty marrow. This hypothesis would explain why some researchers observed a homogeneous change in signal intensity [15] while others observed a non-homogeneous pattern [16]. We observed minor variations in the homogeneity but did not further classify these variations into subgroups.…”
Section: (Arrows)contrasting
confidence: 62%
See 2 more Smart Citations
“…Infiltration and replacement of the hematopoietic marrow by fibrotic tissue results in a lowering of marrow signal intensity on MRI of all conventional sequence types [34,35]. The diminished signal intensity on T2-weighted images is a feature that is also observed in Gaucher's disease [36]. In preleukemic conditions, MRI contributes to the assessment of the prognosis.…”
Section: Myelofibrosis and Other Related Diseasesmentioning
confidence: 99%